Answer:
16
Step-by-step explanation:
First, substitute the values of the variables into the expression:
3(y + 4) - (x - 1)
3(2 + 4) - (3 - 1)
Now, simplify both parentheses:
3(6) - 2
18 - 2
Finally, simplify:
16
Answer:
La mediana es 79 la moda es 87 la media 87 y él rango es 26
Step-by-step explanation:
Espero te ayude ;)
-4x + 2x = -2x
6 + 5 = 11
Therefore, 11 - 2x = 0
11 = 2x
x = 11/2 = 5.5
Answer:
72 +1 , If u = A 8 1 - 2 ( ( + + +1 )– flog ( 3 + 3 / 3 ) ? v1m * + n + 13 ) 4 1 ; then 2 If c ... of any number of such MATHEMATICS . triangles ; and ( 3 ) find the mean value of ... 72 = 62 + 69 , 73 = 82 + 39 , 75 = 72 + 52 . the in - centre and centroid . ... 4n + 1 , or 4n + 2 ,
Step-by-step explanation:
We are supposed to explain why the given function can be expressed in form
, when
.
Since the given function is an exponential function we can express it as
.
Now let us substitute x=0 in the given function,
![f(x)=b^{x}](https://tex.z-dn.net/?f=f%28x%29%3Db%5E%7Bx%7D)
Let us substitute x=0 in our function.
Upon substituting a=1 in our function we will get,
![f(x) =(b)^{x}](https://tex.z-dn.net/?f=f%28x%29%20%3D%28b%29%5E%7Bx%7D)
Therefore, our function f can be represented by the formula of the form
.